'The ghost of environmental history': Analysing the evolving governance of communal rangeland resources in Machubeni, South Africa. Issue 4 (7th April 2022) - Falayi, Menelisi; Gambiza, James; Schoon, Michael
Abstract: The need to effectively govern and manage communal rangeland resources has become more important over the past two decades, given the extent of biodiversity loss caused by a myriad of drivers interacting at different scales. Using in‐depth interviews, participant observations and historical information from organisational records, we analysed the application of governance objectives between 1947 and 2017 and their corresponding rangeland condition outcome in Machubeni (South Africa) communal lands. The results show that while the application of governance objectives varied through time, there has been a steady degradation of local rangeland resources since apartheid, due to internal and external drivers of change. This reveals a disconnection between management and resource conditions, suggesting that a return to effective governance alone will not necessarily result in improved rangeland condition in Machubeni, but that more radical steps such as prolonged periods of resting, reseeding and building individual and group agency, are needed. These findings can help practitioners working in post‐colonial territories to design effective rangeland management models. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary can be found within the Supporting Information of this article.